Menentukan Tingkat Produksi Bakso Dari Tahun 2019-2020 Dengan Teknik Artificial Intelligence Menggunakan Metode Fuzzy Mamdani - Diana Dwi Aulia; Warisa Warisa (Infotek: Jurnal Informatika dan Teknologi, 2021)
AbstractThe increase in sales of meatballs from year to year, seen from a strategic location point of view, and the relatively cheap selling price of meatballs among the community, this meatball shop is a place to eat that is never empty of people visiting to eat. In the business world, actors or business owners are always looking for new opportunities in developing their business, therefore business owners will easily find customers. The more developing or increasing meatball stalls, with this the author aims to see the increase, sales, and customer demand in the meatball shop. And because of the large number of customers, it will definitely increase the material and production costs. In this study, data processing was made using the Mamdani fuzzy method or what is commonly called the Min-Max method. To get the largest production cost output in 2019 - 2020, it can be obtained from the calculation of production costs and the results of available products with several stages of the necessary methods, namely; a) Formation of fuzzy sets; b) Application function implication; c) Composition of rules; d) Defuzzification. The results of defuzzification, we can determine the increase in the production of meatball stalls.